Effect of whitening toothpaste and toothpowder on nanofiller composite resin discoloration after immersion in black tea - Sucanto, Felicia; Ariwibowo, Taufiq; Amin, Meiny Faudah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: One of the factors of discoloration on composite resin is extrinsic factors, such as black tea. Various ways are used to restore the color of composite resin, for example, toothpaste or toothpowder with whitening ingredients. Adding whitening ingredients such as activated charcoal or pearl essence in toothpaste or toothpowder can remove pigments, chromophores, and stains on composite resin with an abrasion effect on the composite surface.Method: This research was an experimental laboratory with a pretest and post-test control group design. This study used 12 samples of nanofiller composite resin (Palfique LX5 B1) in a cylindrical shape with 10 mm diameter and 2 mm thickness. The research was conducted by immersing the samples in black tea for 4 hours with repetition for 13 days. After immersing, the samples were divided into 3 groups: group I was brushed with charcoal toothpaste, group II was brushed with whitening toothpowder, and group III was brushed with non-whitening toothpaste. Brushing was done for 3 minutes with repetition for 13 days. The color parameters were measured using VITA Easyshade V 3 times.Result: The Shapiro-Wilk normality test showed the data normally distributed (p>0,05). The repeated ANOVA test showed no significant color change (p>0,05).Conclusion: Charcoal toothpaste, whitening toothpowder, and non-whitening toothpaste affect the color change of nanofiller composite resin, but there is no significant color change between the three kinds of toothpaste.